Makatang mandirigma, mandirigmang makata si Benigno Ramos sa kasaysayan ng Pilipinas - Ramos, Benigno 1893-1945? (Bahay-Saliksikan ng Bulacan, 2009)
The works and life of Benigno R. Ramos, a warrior who strongly advocated reforms and independence of the Philippines. He was also a noted Filipino author, writer, organization founder, educator, and politician.